The Core Test Wrapper Handbook Rationale and Application of IEEE Std. 1500$1!" (B/s - Silva, Francisco da.; McLaurin, Teresa; Waayers, Tom.; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
The Core Test Wrapper Handbook: Rationale and Application of IEEE Std. 1500TM provides insight into the rules and recommendations of IEEE Std. 1500. The authors present background information about some of the choices and decisions made throughout the design of this IEEE standard conceived to enable efficient core test reuse and debug at the SOC level. The Core Test Wrapper Handbook: Rationale and Application of IEEE Std. 1500TM focuses on practical design considerations and design choices inherent to the application of IEEE Std. 1500. This book teaches an engineer how to add a 1500 wrapper to their core in easy to understand steps. Starting with a bare core (a core without 1500 wrapper), the book progressively builds a 1500 compliant wrapper around this core while discussing overall requirements for each portion of the 1500 wrapper. The Core Test Wrapper Handbook: Rationale and Application of IEEE Std. 1500TM is a very valuable reference for professionals and researchers in the areas of design for test, design for test reuse/design reuse, and SOC implementation.
What is the IEEE 1500 Standard? -- Why use the IEEE 1500 Standard? -- Illustration Example -- Design of the IEEE 1500 Interface Port -- Instruction Types -- Design of the WBR -- Design of the WBY -- Design of the WIR -- Hierarchical Cores -- Finalizing the Wrapper Solution for the EX Core -- SOC Integration of 1500 Compliant Cores.
Keywords: Engineering; Computer-aided engineering; Electrical engineering; Electronics; Microelectronics; Electronic circuits; Engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design; Electronics and Microelectronics, Instrumentation; Electrical Engineering; Electronic books